The impact of organizational commitment on knowledge management processes in project-based organizations with the mediating role of employee motivation - Rastegar, Masoumeh (2023)
The purpose of this research is to investigate the effect of organizational commitment (with three dimensions of emotional commitment, continuous commitment, and normative commitment) on knowledge management processes (KMP) in project-based organizations, considering the mediating role of employee motivation. This research has an applied purpose and a descriptive and quantitative nature, which was conducted with a survey strategy. The statistical population is managers and experts of first-class construction companies in Tehran. Data collection was done through a standard questionnaire with 58 questions and hypotheses were tested with SmartPLS. The findings showed that emotional commitment and continuous commitment have a positive effect on employee motivation in project-oriented organizations, respectively, 0.56 and 0.2. Also, employee motivation has a positive effect of 0.51 on KMP in project-oriented organizations. Therefore, employee motivation plays a mediating role in influencing the dimensions of organizational commitment to KMP. But normative commitment does not have a positive effect on employee motivation in project-oriented organizations. On the other hand, employee motivation is influenced by their commitments to the organization and will have positive effects on intellectual capital management, KM and ultimately business performance. Among research backgrounds, the effect of organizational commitment dimensions on improving KMP with the mediating role of employee motivation in project-oriented organizations has not been investigated. It is expected that the results of this research can finally provide scientific and executive solutions to improve the performance of project-oriented organizations through the improvement of these components.